2005
DOI: 10.1002/ajmg.a.30684
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypes with GATA4 or NKX2.5 mutations in familial atrial septal defect

Abstract: Recently, GATA4 and NKX2.5 were reported as the disease genes of atrial septal defect (ASD) but the relationship between the locations of their mutations and phenotypes is not clear. We analyzed GATA4 and NKX2.5 mutations in 16 familial ASD cases, including four probands with atrioventricular conduction disturbance (AV block) and two with pulmonary stenosis (PS), by PCR and direct sequencing, and examined their phenotypes clinically. Five mutations, including two GATA4 and three NKX2.5 mutations, were identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
128
0
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 194 publications
(132 citation statements)
references
References 35 publications
3
128
0
1
Order By: Relevance
“…27 Mutations in GATA4 TAD regions have been related to septal defects in different studies. 10,17 This study found that the identified mutation in GATA6 TAD region was also associated with ASDs, further supporting the point of a redundant role between GATA4 and GATA6 in cardiogenesis as mentioned earlier. 7,20,21,27,28 A disrupted interaction between GATA4 and TBX5 is involved in ASDs in both humans and mice.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…27 Mutations in GATA4 TAD regions have been related to septal defects in different studies. 10,17 This study found that the identified mutation in GATA6 TAD region was also associated with ASDs, further supporting the point of a redundant role between GATA4 and GATA6 in cardiogenesis as mentioned earlier. 7,20,21,27,28 A disrupted interaction between GATA4 and TBX5 is involved in ASDs in both humans and mice.…”
Section: Discussionsupporting
confidence: 86%
“…9 Numerous mutations in GATA4 have been recognized in a wide range of cases, including tetralogy of Fallot (TOF), pulmonary stenosis, atrial septal defects (ASDs), ventricular septal defects, atrioventricular septal defects and patent ductus arteriosus. 4,[10][11][12][13][14][15][16][17] GATA6 is another member of the GATA family with expression and functions that overlap with GATA4 during cardiovascular development. 7 Recent experiments in animals have revealed critical roles for GATA6 in the development of the myocardium and cardiac morphogenesis, highlighting the potential involvement of GATA6 mutations in the pathogenesis of human CHD.…”
Section: Introductionmentioning
confidence: 99%
“…Screening for mutations of SEMA3C and PLXNA2 may provide further evidence of the involvement of semaphorin-plexin signaling in human OFT defects. It is of note that GATA6 mutations identified in humans were associated with PTA, in contrast with GATA4 mutations, which are commonly associated with atrial and/or ventricular septal defects (20)(21)(22). This result suggests that GATA6 may play a dominant role in OFT development, although Gata6 has been reported to have a redundant role with Gata4 during cardiogenesis (25,(34)(35)(36).…”
Section: Discussionmentioning
confidence: 97%
“…Establishment of genomic bank with cell lines, extraction of genomic DNA samples were reported previously (21,41). All exons and flanking introns of GATA6 were PCR amplified and sequenced using direct, bidirectional sequencing; a detailed procedure is given in SI Materials and Methods.…”
Section: Mutation Analysis and Clinical Evaluation Of Patientsmentioning
confidence: 99%
See 1 more Smart Citation